Politik Uang (Money Politic ) dalam Pemilihan Walikota Kendari Tahun 2017 - La Way . (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2017)
This study examines the Money Politic in the selection of Kendari mayor in 2017. The focus of the problem in this research is consisted of three, namely the influence of money politics on the choice of society, what are the forms of money politics and how the public view of money politics in the election of Kendari mayor. The purpose of this study is to know and analyze whether there is a political influence of money on the choice of society, to know and analyze the form of money politics and to know and analyze the views of society on money politics. The theory used in this research is the theory of Rational choice by Max Weber and the theory of needs by Maslow. Methodologically, this research is a qualitative research with data collection which is done with the technique of observation and in-depth interview. The results of this study found facts on the ground that the form of money politics with the evidence obtained is money, rice, 1 (one) set of sound system and a number of seats by the successful team is true, namely in Lepo-Lepo sub district of Baruga and Rahandouna subdistrict of Poasia, in Mataiwoi Sub district of Wua -Wua, Wawowanggu sub-district of Kadia, Mandonga sub-district of Mandonga, Powatu sub district of Powatu, Ponggaloba Sub district of West Kendari and every district in Kendari city. This behavior is influenced by factors such as poverty, societal ignorance of politics and cultural factors. The effect on the choice of society is not significant because there are pros with money politics and there is also a counter with the money politics in every election. While the view of money politics in Kendari mayoral election is very diverse that there is a positive outlook because in every election has become toxicity (already entrenched) and the second is negative because it destroys the democratic democracy because it is chosen not because of the ability, capability and morality of the candidate but because of the money. Keywords: public election, voter behaviour, money politic